The “Disappearing” of Croatian Art in Hungarian Art Exhibitions at the Turn of the 20th Century - Samuel David Albert (Arts)
This article examines the place of Croatian art within Hungarian art exhibitions around the turn of the century. Over close to a decade, from the 1896 Millennial Exhibition until the 1904 St. Louis World’s Fair, the way Croatian art was displayed within Hungarian exhibitions had changed. While it might seem that the ultimate absence of Croatian art in later Hungarian displays is an example of Hungarian chauvinism, the opposite is the case: Croatian art still continued to be displayed, but not as a subsidiary of Hungarian art.